Identification of lactic acid bacteria isolated from Thai fermented sausage for nitrite degradation ability - Wanangkarn, A.; Tan, F. J.; Phumthong, N. (International Journal of Agricultural Technology, 2020)
Many traditional Thai fermented meat products were naturally fermented, relying on the natural contamination by house flora resulting in products with inconsistent qualities and unsafe products. The lactic acid bacterial species in Thai fermented sausage (E-sarn sausage) was identified by using molecular techniques and investigated their potential to reduce the nitrite content. The isolated strains were identified by sequencing 16S ribosomal DNA as Enterococcus durans, Lactobacillus plantarum, Lactobacillus brevis, and Pediococcus pentosaceus. The nitrite degradation capacity in MRS broth, E. durans, L. plantarum, L. brevis, and P. pentosaceus could degrade 89.35%, 79.11%, 86.22% and 72.87% of the initial nitrite concentration, respectively. The nitrite concentration decreased throughout fermentation time and exhibited the lowest final value as 12.78-32.28 µg/ml at the third day. These results suggested that lactic acid bacteria isolates from E-sarn sausage had showed a potential as starter culture to reduce the residual nitrite in Thai fermented meat products.